Highly Synergistic Effects of Melittin With Vancomycin and Rifampin Against Vancomycin and Rifampin Resistant Staphylococcus epidermidis - Mirzaei, Rasoul; Alikhani, Mohammad Yousef; Arciola, Carla Renata; Sedighi, Iraj; Irajian, GholamReza; Jamasbi, Elaheh; Yousefimashouf, Rasoul; Bagheri, Kamran Pooshang (Frontiers in Microbiology, 2022)
Methicillin-resistant Staphylococcus epidermidis (MRSE) strains are increasingly emerging as serious pathogens because they can be resistant to many antibiotics called multidrug resistance (MDR) that limit the therapeutic options. In the case of vancomycin- and rifampin-resistant MDR-MRSE, the physicians are not allowed to increase the doses of antibiotics because of severe toxicity. Accordingly, we investigated the synergistic activity of melittin antimicrobial peptide with vancomycin and rifampin against vancomycin-resistant, and rifampin-resistant MDR-MRSE isolates. Minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), fractional inhibitory concentration index (FICi), and fractional bactericidal concentration index (FBCi) of antimicrobial agents against isolates were determined. Coagulate activities and serum and salt stability as well as melittin cytotoxicity on human embryonic kidney (HEK) 293cells and human Red blood cells (RBCs) at their synergistic concentrations. MIC and MBC values for melittin were in the range of 0.312-2.5 and 0.312-5, respectively. Results also showed that the interaction of melittin with drugs was highly synergistic in which the geometric means of FICi and FBCi were <0.5. Induced synergism led to a decrease in melittin, rifampin, and vancomycin concentrations by 8-1020, 2-16, and 4-16-folds, respectively. This phenomenon caused a reduction in melittin toxicity by which the synergistic concentration of melittin needed to kill bacteria did not show cytotoxicity and hemolytic activity. Besides, no coagulation activity was found for the synergistic and alone concentrations of melittin in both Prothrombin Time (PT) and Partial Thromboplastin Time (PTT). Interestingly, the antibacterial activity of melittin in Mueller Hinton Broth (MHB) containing human serum did no significant differences between MIC and MBC values of melittin in MHB and MHB containing 10 % human serum. The present findings showed that the therapeutic index of melittin was improved by 32.08- and 12.82-folds when combined with vancomycin and rifampin, respectively. Taken together, the obtained data show that melittin alone was effective against MDR-MRSE isolates and this antimicrobial peptide showed highly synergistic effects with vancomycin and rifampin without causing toxicity. Therefore, the combination of melittin and traditional antibiotics could be a promising strategy for the treatment of infections caused by MDR-MRSE.